Thrombolytic therapy as first line treatment in prosthetic mitral valve thrombosis - Potwar, Sushrut; Kothari, Ankur; Potnis, Abhishek; Paranjape, Malavika (International Surgery Journal, 2023)
Background: A very common post-operative mechanical complication of a prosthetic valve is thrombosis leading to valve being stuck. This leads to rapid development of heart failure and can result in sudden death of the patient in an aggravated manner. The study aims to put forth the importance of immediate thrombolysis in such patients which can provide bridging between the event and immediate surgery. Methods: A total of 50 patients were retrospectively studied after presentation with prosthetic valve thrombosis and the thrombolytic agent used in all the cases was injectable streptokinase or urokinase. Post streptokinase patients were given heparin infusion and oral anticoagulants. The therapy was considered failure if transvalvular gradients decreased less than 50% or in case of persistent valve motion abnormality. Results: 94% patients had complete normalisation of valve function and decrease in transvalvular gradients to less than 50% within the first 24 hours. 4% patients required surgery and 2% patients could not survive the treatment. Conclusions: Immediate thrombolysis on presentation has shown significant improvement in survival without the risk of subjecting patients to redo surgeries which are associated with multiple complications in the perioperative period.